Koherensi Pembangunan Lingkungan Yang Berkelanjutan Dalam Perizinan Pengusahaan Tambang Batuan - Bima Setya Aji; Lego Karjoko; Fatma Ulfatun Najicha (Faculty of Law Universitas Sebelas Maret Surakarta, 2022)
This legal research has aims to see how the implementation of the principles of sustainable living development in mining business licensing if reviewed by the Regional Regulation of the Central Java Province number 10 of 2011 concerning the management of mineral and coal mining towards the implementation of rock mining business permits. This legal research is a prescriptive type of normative legal research using a statute approach. The types of legal materials used are in the form of primary and secondary legal materials. The technique of collecting legal materials used is literature study techniques, while the technique of analyzing legal materials used is the deduction method. The results of this legal research indicate that the implementation of the principles of sustainable environmental development in mining business licensing has been included in several articles in the Regional Regulation of Central Java Province number 10 of 2011 concerning the management of mineral and coal mining. This conclusion has obtained from the analysis there are several articles including: First, article 1 number 38 requires that every mine must have an AMDAL study. Second, article 1 number 39-42 regulates reclamation and post-mining activities. Third, Article 2 which regulates mining principles. Fourth, Article 3 which contains the objectives of mineral and coal management. licensing instrument that must be owned by stones mining are mining business permits, mining business area permits, environmental permits, reclamation approvals, and post-mining approvals